Korelasi Kinerja Dosen Dengan Organizational Citizenship Behaviour (OCB) di IAIN Kediri - Muawanah (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2023)
Organizational commitment is personal responsibility and involvement in the organization, which includes trust, support for organizational objectives and values, and sincerity for the organization's formed interests. Through emotional and ongoing commitment, OCB is a unique aspect of individual functioning at work, such as the desire to cooperate, assist each other, advise, actively participate, provide additional services for those who use services, and make efficient use of one's working time. This study examines the relationship between organizational commitment and organizational citizenship behavior (OCB) and the performance of lecturers at IAIN Kediri. The findings of this study revealed a number of conclusions. 1) There is a link between organizational commitment and lecturer performance at IAIN Kédiri; 2) there is a link between organizational citizenship behavior (OCB) and IAIN Kediri teacher performance; and 3) there is a link between organizational commitment, organizational citizenship behavior (OCB), and speaker performance. Therefore, empirical evidence suggests that lecturer performance will be influenced by organizational commitment and organizational citizenship behavior variables.